Effectiveness of Forgiveness Therapy on Emotional Expression in Mother with Visual Impairment Children - Hosseini, Maede; Ashori, Mohammad (Psychological Research in Individuals with Exceptional Needs, 2025)
The ability of human relationships to continue healthily depends on individuals being aware of their emotions and being able to express them correctly. So, determining the variables that affect the emotional expression that are effective throughout individuals’ lives can contribute to the positive maintenance of human relationships. This research aimed to investigate the effectiveness of forgiveness therapy on emotional expression of mothers with visually impaired children. The present research was applied in terms of purpose and quasi-experimental in terms of method, it was a quasi-experiment with a pre-test and post-test design with a control group. The total number of the statistical population was 90 people, 20 of the mothers were selected by convenience sampling method from schools for the blind in Isfahan city and were randomly replaced in a control group and an experimental group of 10 people. forgiveness therapy was provided to the experimental group in 12 sessions, while the control group did not receive any training until the end of the post-test phase. Participants were assessed using the Measure of Emotional expression questionnaire King and Emmons (1990). The obtained data were analyzed by analysis of covariance using SPSS 26 software. The findings indicated that forgiveness therapy approach had a positive and significant effect on emotional expression and on the expressing emotion subscales (expressing positive emotion, intimacy, and expressing negative emotion) of mothers with visually impaired children. Therefore, it can be concluded that the forgiveness therapy reduces expressing negative emotion and improves expressing positive emotion and intimacy of these mothers.